Race/ethnicity difference in the pharmacogenetics of bilirubin-related atazanavir discontinuation. Issue 1 (January 2018) - Leger, Paul; Chirwa, Sanika; Nwogu, Jacinta N.; Turner, Megan; Richardson, Danielle M.; Baker, Paxton; Leonard, Michael; Erdem, Husamettin; Olson, Lana; Haas, David W.
Abstract : Background: Atazanavir causes plasma indirect bilirubin to increase. We evaluated associations between Gilbert's polymorphism and bilirubin-related atazanavir discontinuation stratified by race/ethnicity. Patients and methods: Patients had initiated atazanavir/ritonavir-containing regimens at an HIV primary care clinic in the southeastern USA, and had at least 12 months of follow-up data. Metabolizer group was defined by UGT1A1 rs887829 C→T. Genome-wide genotype data were used to adjust for genetic ancestry in combined population analyses. Results: Among 321 evaluable patients, 15 (4.6%) had bilirubin-related atazanavir discontinuation within 12 months. Homozygosity for rs887829 T/T was present in 28.1% of Black, 21.4% of Hispanic, and 8.6% of White patients. Among all patients the hazard ratio (HR) for bilirubin-related discontinuation with T/T versus C/C genotype was 7.3 [95% confidence interval (CI): 1.7–31.5; P =0.007]. Among 152 White patients the HR was 14.4 (95% CI: 2.6–78.7; P =0.002), but among 153 Black patients the HR was 0.8 (95% CI: 0.05–12.7; P =0.87). Conclusion: Among patients who initiated atazanavir/ritonavir-containing regimens, UGT1A1 slow metabolizer genotype rs887829 T/T was associated with increased bilirubin-related discontinuation of atazanavir in White but not in Black patients, this despite T/T genotype being more frequent in Black patients.